Photovoltaic Properties and Negative Capacitance Spectroscopy of PCBM:P3HT/FTO Nanostructured Counter Electrode for TiO2-Based DSSC - Yahia, I. S.; Mansour, Sh. A.; Hafez, Hoda S.; Ocakoglu, K.; Yakuphanoğlu, Fahrettin (Springer, 2012)
Nano-clusters blind films of phenyl C61-butyric acid methyl ester (PCBM) and poly(3-hexylthiophene) (P3HT) were deposited on fluorine doped tin-oxide (FTO) substrate by spin coating and applied as counter electrodes instead of platinum for a new FTO/TiO2 + K30 dye-sensitized solar cell. The photovoltaic parameters of the fabricated solar cell; open circuit voltage, short circuit current, output power and fill factor, were studied under various light intensities in the range 20:110 mW cm(-2). An impedance spectroscopy study was also performed in a wide frequency range (5 kHz-1 MHz) to study the electron transport properties of the solar cells. The capacitance-voltage of the prepared DSSC is characterized by two parts: positive values of capacitance at low frequency range, f a parts per thousand currency sign 100 kHz and negative capacitance i.e., an inductive behavior, in higher frequency range f a parts per thousand yen 300 kHz Conducting polymer electrode based on PCBM:P3HT/FTO can be used as a counter electrode in a DSSC.
Keywords: DSSC; PCBM:P3HT; K30 dye; Photovoltaic properties; Impedance spectroscopy; Negative capacitance